Coach Knowledge Management: The Needs and Wants of Elite Coaches from African and Small Island Regions of the Commonwealth - Patry, Philippe (Université d'Ottawa / University of Ottawa, 2016)
Coaching knowledge is an essential resource for improving competition quality. The purpose of this study was to explore the needs and wants of elite coaches from the African and small island regions of the Commonwealth at the 2014 Commonwealth Games in Glasgow, Scotland. Specifically, their development of coaching knowledge and their context was analyzed to understand their needs and wants. Using a knowledge management framework, 19 semi-structured interviews identified the process of combining knowledge as predominant in the development of coaching knowledge within these regions. Tacit knowledge was developed through their social environment, mentorship, and athletic or coaching experience. The need for formal knowledge development opportunities and basic coaching resources were also identified. Finally, technology helped to reduce challenges around accessibility to knowledge, and coach certification programs helped with the transition from athlete to coach.
Keywords: Knowledge management; knowledge type; coach knowledge; coach learning; coach development; Commonwealth Games; Commonwealth Games Federation